The digital shift in parental strategies for heritage language maintenance among expatriate families in Saudi Arabia - Musa Alghamdi; Said Muhammad Khan; Shazia Hamid; Saira Abbas (Institute of Advanced Engineering and Science, 2026)
Around two-fifths of the population living in Saudi Arabia consists of expatriates. However, there is limited research on how these families maintain their heritage languages (HLs) in a digital world with limited institutional support. Maintaining HLs is important for identity, cultural continuity, and a sense of belonging across generations, especially for families living far from home. This qualitative study explores how expatriate parents in Saudi Arabia use digital tools to help their children maintain HLs, using Fishman’s reversing language shift (RLS) framework and family language policy (FLP) theory. Researchers interviewed 36 expatriate parents from 15 different national and linguistic backgrounds and analyzed the data with reflexive thematic analysis in NVivo. The results show that families are moving from exclusively home-based language practices to a mix of digital strategies, such as apps, video calls, and online learning spaces, which help strengthen cross-border connections and increase language exposure. However, these new practices also increase mothers’ workload, as they take on most of the planning, mediation, and emotional support. The study suggests policy and practical steps that fit with Saudi Arabia’s Vision 2030, such as providing subsidized multilingual digital resources and family-focused support programs. The clear research design makes the study easy to replicate, and future research should include lower-income families, children’s views, and long-term studies of digital family language practices.